Báo cáo giải trình, tiếp thu, chỉnh lý dự thảo Luật Cảnh sát cơ động (Số: 243/BC-UBTVQH15) - Ủy ban Thường vụ Quốc hội (2022)
Toàn văn Báo cáo giải trình, tiếp thu, chỉnh lý dự thảo Luật Cảnh sát cơ động (Số: 243/BC-UBTVQH15)